Analisis Bank Digital Terhadap Pertumbuhan Minat Menabung - Rosi Julianti (2021)
Technological developments that occur today can be seen in industrial progress in various fields, especially banking. The most visible progress in the banking industry is the appearance of digital banks. This digital bank is favored by society because it is proven to make it easier for them to carry out activities related to banks. This paper aims to compare the customers interest in saving in non-digital commercial banks and digital banks. The method used in this paper is the purposive sampling method using a questionnaire. The results show that customers prefer the saving feature in digital banks compared to non-digital commercial banks. However, regarding the frequency of savings made by customers, customers make deposits at non-digital commercial banks more often than digital commercial banks, this is assumed because customers do not fully trust the security of digital banks.